IMPLEMENTASI INTERNET OF THINGS PADA SISTEM KENDALI LAMPU RUMAH MENGGUNAKAN TELEGRAM BOT & NODE MCU ESP8266 - zakwansyah; Satria Syuhada (Politeknik Aceh, 2023)
The house light control system is manually operated, tends to forget turn off the lights when leaving the house, house owner must return to turn off the lights or leave the lights on until the houseowner returns. The use of NodeMCU ESP8266 is currently favored by internet of things based developers, other reason is the price of the module was quite cheap and programmed using the Arduino IDE allowing NodeMCU be the preferred choice. The study uses Telegram Messenger Bot as a message sender and message recipient to control home lights, using NodeMCU as a Relay controller to turn 0n - off the home lights remotely. This system can be controlled from any distance, according to tests that have been carried out this system can operate from a distance of 100 meters, 5 kilometers, even from outside the area with a distance of 2193 kilometers.